Edukasi Makanan Sehat dengan Metode Bercerita pada Anak Usia Dini - Esti Nur Janah; Siti Fatimah; Adinda Alya Sheravina; Renita Juni Yanti Putri Pratam (Lembaga Pengembangan Kinerja Dosen, 2025)
Lack of knowledge about nutrition makes children buy food without knowing whether the food contains sufficient nutrition or not. In fact, food has an important role in children's growth and development because it is the main builder of growth and development. Nutrition education is very much needed to improve children's knowledge and behavior. The storytelling method is one of the educational methods that can be used in an effort to teach students a healthy lifestyle, including about healthy food. The purpose of this community service is to increase students' knowledge about healthy food by using the storytelling method so that children are expected to behave healthily by consuming healthy food and snacks. Community service was carried out at Bambini School Paguyangan with 19 students aged 3-6 years. The activity went well, there was an increase in children's knowledge about healthy food and participants were very enthusiastic in answering questions. Healthy food education can also prevent students from buying snacks carelessly and choosing healthy foods. Healthy food education regarding the selection of healthy foods is expected to create a healthier generation.